The effects of school bullying on the victims of bullying from the point of view of teachers and ways to confront it: A field study on a sample of teachers in Al Shula private schools in the city of Sharjah - Al-dhuhoori, Khadija Ali; Yaiche, Ouassila (Al-Adab Journal, 2022)
The current study aimed to identify the social, psychological and educational effects of school bullying on bullying victims, and the ways to reduce them from the point of view of teachers in the Emirate of Sharjah. The study relied on the social survey method, using a simple random sampling method, and the number of its items was (100) male and female teachers working in Al-Shula schools in the Emirate of Sharjah, and a questionnaire was used to collect information.The study reached a set of results, the most important of which are:The social effects of school bullying on bullying victims ranked first with an average of (2.62), most notably: the victims' lack of social communication skills with others, and the lack of access to social support. Followed by the psychological effects with an average of (2.60), most notably: the inability to self-defend; The tendency to be isolated and introverted, poor self-confidence and low self-esteem. While the educational effects ranked third, with an average of (2.51), most notably: low academic achievement, difficulty to concentrate while teachers are explaining, and withdrawal from extracurricular activities.The methods of confrontation proposed by teachers to curb the phenomenon of school bullying were: involving students in extra-curricular activities and voluntary work, strengthening the role of social and psychological specialists in schools, and holding meetings and discussions between the school administration and students’ parents.